Pediatric Sensorineural Hearing Loss, Part 2: Syndromic and Acquired Causes - Huang, B.Y.; Zdanski, C.; Castillo, M. (American Journal of Neuroradiology, 2012)
SUMMARY: This article is the second in a 2-part series reviewing neuroimaging in childhood SNHL. Previously, we discussed the clinical work-up of children with hearing impairment, the classification of inner ear malformations, and congenital nonsyndromic causes of hearing loss. Here, we review and illustrate the most common syndromic hereditary and acquired causes of childhood SNHL, with an emphasis on entities that demonstrate inner ear abnormalities on cross-sectional imaging. Syndromes discussed include BOR syndrome, CHARGE syndrome, Pendred syndrome, Waardenburg syndrome, and X-linked hearing loss with stapes gusher. We conclude the article with a review of acquired causes of childhood SNHL, including infections, trauma, and neoplasms. BORbranchio-oto-renalCISSconstructive interference in steady stateIACinternal auditory canalNF-2neurofibromatosis type IISCCsemicircular canalSNHLsensorineural hearing lossT1WIT1-weighted imageT2WIT2-weighted image